Natural Gas Pipeline Flow Calculations - Bengtson, Harlan (McGraw-Hill's AccessEngineering., 2014)
This Excel workbook streamlines normally time-consuming natural gas pipeline flow calculations by automating the iterative calculations of gas outlet or inlet pressure. The workbook supports 3 different equations for natural gas pipeline flow calcuations: the Weymouth Equation, the Panhandle A Equation and the Panhandle B Equation. Worksheets are included to calculate: 1) natural gas flow rate 2) required pipe diameter 3) outlet gas pressure 4) inlet gas pressure. The iterative calculations needed to determine gas outlet pressure or gas inlet pressure are facilitated using Excel's Goal Seek tool. There is also a worksheet for calculation of the natural gas density, viscosity, and compressibility factor, based on inputted values for temperature, pressure and specific gravity of the gas.